"Most heterodox economists still think that feminist questions relate to 'special issues'". Interview with Professor Diane Elson - Diane Elson (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2005)
First paragraph: You are well-known in Germany as an economist who has been also dealing with feminist issues for – compared to German scientists – a relatively long period of time, as in your article on market socialism published in 1990. How did you come across feminist subjects at such an early point in time – at least for (German) economists?
Keywords: 330